Praktik Pengungkapan Emisi: Studi Empiris Lima Nominator ISRA sepanjang 2007-2016 - Christya Nur Febriani; Arthik Davianti (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2018)
The objective of this study is to explore emissions disclosures by five Indonesian Sustainability Reporting Awards (ISRA) nominee companies and to indicate disclosure items proper for condition in Indonesia. This research utilized a case study approach regarding five ISRA nominees during 2007-2016, which included both public and private mining companies. The study applied content analysis techniques with the Global Reporting Standard 2016 as content guidelines. The results showed indication type of industry impact towards the emission disclosures practice, particularly the extent of emissions disclosures.